Psychological Factors Influencing Tourist Decision Making: A Qualitative Review in the Context of Business Psychology - Damiasih, D. (Manunggal Halim Jaya, 2025)
This qualitative study examines the psychological factors influencing tourist decision-making processes within business psychology. The research explores the interplay of motivational factors, perceived risk, destination image, emotions, culture, and technology in shaping tourist behaviors and preferences. The research methodology involves a systematic literature review utilizing qualitative analysis techniques such as thematic analysis, content analysis, and narrative analysis. Data were collected from scholarly works, including peer-reviewed journal articles, books, and conference papers. The analysis synthesizes key insights and identifies recurring themes across the literature. The findings highlight the significance of motivational factors, perceived risk, destination image, emotions, culture, and technology in influencing tourist decision-making processes. Specifically, motivational factors emerge as crucial determinants of tourist preferences, with hedonic motives driving leisure travelers and utilitarian motives guiding business travelers. Perceived risk and destination image are pivotal in shaping tourist attitudes and behaviors, while emotions are potent decision-making drivers. Cultural influences and technological advancements further impact tourist behaviors and preferences, emphasizing the importance of cultural sensitivity and digital marketing strategies in destination management. The study provides valuable insights for theoretical advancement and practical application in the tourism industry, informing destination marketers, managers, and other stakeholders in developing tailored strategies to attract tourists and enhance destination competitiveness.